High Levels of Antibiotic Resistance in MDR-Strong Biofilm-Forming Salmonella Typhimurium ST34 in Southern China - Yuan Gao; Kaifeng Chen; Runshan Lin; Xuebin Xu; Fengxiang Xu; Qijie Lin; Yaping Hu; Hongxia Zhang; Jianmin Zhang; Ming Liao; Xiaoyun Qu (Microorganisms, 2023)
Salmonella enterica subsp. enterica serovar Typhimurium (S. typhimurium) is an important zoonotic pathogen with important public health significance. To understand S. typhimurium’s epidemiological characteristics in China, multi-locus sequence typing, biofilm-forming ability, antimicrobial susceptibility testing, and resistant genes of isolates from different regions and sources (human, food) were investigated. Among them, ST34 accounted for 82.4% (243/295), with ST19 ranking second (15.9%; 47/295). ST34 exhibited higher resistance levels than ST19 (p < 0.05). All colistin, carbapenem, and ciprofloxacin-resistant strains were ST34, as were most cephalosporin-resistant strains (88.9%; 32/36). Overall, 91.4% (222/243) ST34 isolates were shown to have multidrug resistance (MDR), while 53.2% (25/47) ST19 isolates were (p < 0.05). Notably, 97.8% (45/46) of the MDR-ACSSuT (resistance to Ampicillin, Chloramphenicol, Streptomycin, Sulfamethoxazole, and Tetracycline) isolates were ST34, among which 69.6% (32/46) of ST34 isolates were of human origin, while 30.4% (14/46) were derived from food (p < 0.05). Moreover, 88.48% (215/243) ST34 showed moderate to strong biofilm-forming ability compared with 10.9% (5/46) ST19 isolates (p < 0.01). This study revealed the emergence of high-level antibiotic resistance S. typhimurium ST34 with strong biofilm-forming ability, posing concerns for public health safety.